EFL teachers’ cognition of English as a global language: ideologies, identities, and practices - Montakantiwong, A (2020)
The global presence of English as a lingua franca has raised substantial concerns regarding an urgent need for a shift in English language pedagogy. Teachers working within the immense English Language Teaching (ELT) enterprise are now expected to participate in an unprecedented endeavour to better equip learners with both the necessary language skills and the awareness of the ubiquity of English varieties currently used among speakers, native or non-native alike. In light of this changing sociolinguistic scenario, the emerging field of Global Englishes proposes a framework for action, calling for a re-appraisal of the beliefs about English that permeate all aspects of pedagogical practices (Galloway & Rose, 2015; Rose & Galloway, 2019). Such need for a paradigm shift has continued to be voiced in research, but rarely are the very voices of the teachers heard. Little has been discussed about their sense-making of the pedagogical implications of the ideological rhetoric underlying English teaching at the operational level.